Biology and life table of Trichogramma chilotraeae, Egg parasitoids of Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae). Issue 1 (December 2021) - Sari, L; Maryana, N; Hidayat, P
Abstract: Spodoptera frugiperda is a species of armyworm that attacks maize crops globally and is a dangerous new invasive pest in Indonesia. Biological control, which employs natural enemies, is one method of controlling this pest. One of the natural enemies found in the field is the egg parasitoid of the Trichogrammatidae family. This study aimed to determine the reproductive capacity of the parasitoid on S. frugiperda eggs. The tested parasitoids were collected from S. frugiperda eggs on corn cultivations in Tenjolaya Village, Bogor Regency, West Java Province. The identification results showed that the parasitoid species used in this study was Trichogramma chilotraeae . The development periods of eggs, first instar larvae, second instar larvae, and pupae in the laboratory were 1.16 days, 1.18 days, 1.39 days, and 3.28 days, respectively. The reproductive capacity of T. chilotraeae on S. frugiperda eggs, referred to as the net reproduction rate (Ro), was 28.13, gross reproduction rate (GRR) was 30.43. the average time for one generation (T) was 9.07. The intrinsic rate of increase (r) was 5.54, and Doubling time (DT) was 1.88. Thus, the egg parasitoid of T. chilotraeae was not very effective as a potential biological agent for S. frugiperda .